Wspomnienie pośmiertne. Andrzej Mikołajczyk (1948-1991) - Kajzer, Leszek (Acta Universitatis Lodziensis. Folia Archaeologica, 1994)
Assistant Professor Andrzej Mikołajczyk, Director of the Archaeological and Ethnographic Museum in Łódź, died suddenly on 16th January, 1991. Throughout his adult, regretfully short life he was associated with the Department of Archaeology of Łódź University. However, this is not the only reason why his obituary appears in this journal. Andrzej Mikołajczyk studied archaeology under Professor Konrad Jażdżewski, being one of his last and most brilliant students. He graduated from Łódź University in 1970 and took his Ph. D. degree at the Department of Archaeology of this University in 1976. His thesis, Naczynia datowane skarbami monet XIV-XVIII w. na ziemiach polskich (Vessels dated by coin hoards of the 14th-18th centuries in Polish territories) was published m 1977. Following the retirement of Professor Jażdżewski in 1979, he was appointed (on Professor’s suggestion) Director of the Archaeological and Ethnographic Museum in Łódź, a post he held until his untimely death. Professor’s choice proved to be a wise one. Under Mikołajczyka direction the museum not only continued good traditions but also became one of the leading archaeological centres of the eighties in Poland. Andrzej Mikołajczyk found time not only for effective direction of the museum and for research but also for lecturing on basic problems of numismatics at the Department of Archaeology. In 1981 he qualified as assistant professor, his thesis being published in 1980 as Obieg pieniężny w Polsce środkowej w wiekach od XVI do XVIII (Monetary circulation in Central Poland from the 16th to 18th century). This thesis has also established his position as the first numismatist in Poland to undertake studies of numismatics of modern times and of monetary circulation. These two problems became the main subjects of his research. Andrzej Mikołajczyk’s scholarly output is astonishing both on account of its volume and variety. He is the author of 10 books, 11 guides to museum exhibitions and of about 400 articles, a considerable part of which was published in congress languages or abroad (in the former Soviet Union, Great Britain, Spain, Portugal, Italy, Germany, Norway, Denmark, Sweden, Cuba and Hungary). Perhaps this is the reason for a certain paradox – he was better known and thought of more highly by west European numismatists than by the Polish ones, better known in the milieu of numismatists and historians than in that of archaeologists, and finally better known in Poland than in Łódź where he was primarily regarded as museum director. The museum and various scholarly activities did not exhaust his tremendous energy. At the close of the eighties he was elected to the Łódź City Council. As an outstanding personality he dealt successfully with the three speheres of activity. Owing to his wide interest and manifold duties his life was active, intensive, and – as time has proved it – too arduous. He was an exacting boss, demanding, however, more from himself than from his staff, a splendid organizer in the field of museology and scholarly life, always ready to help and to advise. For his friends he was good company and an intelligent causeur. He did not live long enough to attain full professorial rank or to see his various organizational and research projects brought to fruition. Yet his achievements are truly imposing, much more so than those of many a retired professor. The Łódź milieu of humanities has suffered a great loss: there died a remarkable man, a distinguished numismatist, archaeologist, economic historian, museologist, and organizer of scholarly life, deeply involved in the problematics of the cultural and scientific milieu of Łódź. His death left a gap in Polish and European Learning.